Pengukuran Tingkat Kepuasan Pengguna Jasa Parkir di Pusat Pembelanjaan Royal Plaza Surabaya - Mohammad Djaelani; Didit Darmawan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
The purpose of this study is to determine the level of satisfaction of vehicle parking service users at the Royal Plaza Surabaya shopping center. This survey was conducted in the Royal Plaza parking area. Primary data were collected by researchers from the main source, namely users of Royal Plaza parking services by means of interviews and filling out questionnaires. The population in this study are visitors who have used the Royal Plaza parking area. Samples are users of Royal Plaza parking services who meet the requirements of 100 respondents. The finding of this study is that respondents in general tend to have achieved a good level of satisfaction. There are several attributes that need to be developed better and there are attributes that have satisfied users. The attribute that must be maintained as the main element forming satisfaction of parking service users is that the access to the parking location is close to the shopping center and they never go around in the parking area to find a parking space. Parking has met security standards such as cctv and they feel the vehicle will be parked safely